Ultracold cryogenic TEM with liquid helium and high stability - Emily Rennich; Suk Hyun Sung; Nishkarsh Agarwal; Maya Gates; Robert Kerns; Robert Hovden; Ismail El Baggari (Proceedings of the National Academy of Sciences, 2025)
Cryogenic transmission electron microscopy has revolutionized structural biology and materials science. To image below liquid nitrogen temperatures, various liquid helium stages have been constructed but have proven to be complex and unstable, making high-resolution imaging challenging. This problem is even more pronounced in side-entry specimen holders common on modern transmission electron microscopes. Here, we introduce an ultracold liquid helium transmission electron microscope side-entry specimen holder, featuring continuous cryogen flow and vibration decoupling. This instrument is compatible with modern aberration-corrected microscopes and achieves sub-25 K base temperature, ± 2 mK thermal stability over many hours, and atomic resolution—setting the stage for a new era of cryogenic electron microscopy.